PENGAWASAN PENGEMUDI SEPEDA MOTOR DI BAWAH UMUR OLEH SAT LANTAS POLRESTA PEKANBARU - Dewi Purwati; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The high traffic violations and accidents motorcycle drivers in particular underage junior high schoolstudents should not happen given the Law No. Article 77, paragraph 1 and Article 81 paragraph 1 (a)of Law Number 22 Year 2009 on Traffic and Transportation, and Section 24 (a ) and 25 1 (a) thePolice Regulation No. 9 of 2012 on a driver's license that driving a motorcycle under the age of 17years are not allowed. Lack of knowledge of traffic education and awareness in order, security andsafety in driving has led to the rise of motorcycle drivers under age. This study aims to determine howto control the motorcycle driver under age by the Traffic Unit Pekanbaru and determine the factorsthat hinder surveillance motorcycle driver under the age of junior high school students in particular.This study used a qualitative approach to data collection techniques of observation and interviewswith informants obtained from studies that have determined the snowball sampling technique. Wheresupervision motorcycles drivers under age by Traffic Police Unit Pekanbaru is not maximized. This isproven by the many motorcycle drivers were caught underage raids, and the high number of accidentsand violations committed by minors special junior high school studentsKeywords: Monitoring, Motorcycle driver, a minor.